Qualitative Analysis of Caregiver and Patient Experiences with and Barriers to Medical Nutrition Therapy Utilization in Pediatric Type 1 Diabetes - Azova, Svetlana; Michelson, Hannah; Williams, David; Lennerz, Belinda; Garvey, Katharine (Endocrine practice, 2025)
Despite recommendations by major diabetes organizations, medical nutrition therapy (MNT) in pediatric type 1 diabetes (T1D) remains underutilized. Suboptimal prandial practices and limited engagement in nutritional counseling with the diabetes care team may impact health outcomes in these youth. This study aimed to understand patient and caregiver experiences with and barriers to MNT utilization. Utilizing the socioecological framework and the phenomenological research design augmented by grounded theory methods, we conducted semi-structured interviews with caregivers of patients with T1D <18 years and youth with T1D 12-17 years with T1D duration ≥1 year. Emergent themes were used to generate a theoretical model of the relationship between the family unit encompassing the child with T1D and suboptimal MNT utilization. We recruited 9 caregivers and 9 patients. Qualitative analysis yielded important themes highlighting challenges impacting MNT utilization across 5 domains: individual, shared child/caregiver-specific, interpersonal, institutional, and community/societal. The central theme was recognition of the importance of MNT in pediatric T1D management juxtaposed with barriers to its implementation. Factors mediating this paradoxical relationship included the impact of diabetes technologies on prandial practices, balance between caregiver involvement and emerging patient independence, emphasis on normalcy, attempts to match child's way of eating with that of others, school-based considerations, and cultural/sociodemographic influences. This study generated informative insights on the perceptions and experiences of patients and caregivers regarding barriers to MNT implementation in pediatric T1D. Efforts to enhance MNT appreciation and utilization in this population by targeting the identified barriers through patient-/family-centered strategies are crucial.